Destination Brand Storytelling in Thematic Villages Kampung Budaya Polowijen: The Power of Narrative Video - Aprilia Risky Kusumawati; Hiqma Nur Agustina (Kirana Publisher (KNPub), 2026)
Kampung Budaya Polowijen is a thematic village located in Malang, East Java, which represents local cultural heritage originating from Malang. One of the main challenges faced by this thematic village is the limited availability of promotional media that can effectively communicate its cultural richness to a wider audience. This study aims to develop narrative videos using storytelling techniques as a promotional medium to strengthen the destination brand of Kampung Budaya Polowijen. The research applied a design and development approach consisting of analysis, design, development, implementation, and evaluation stages. The resulting narrative videos were evaluated by respondents to assess their effectiveness as a promotional tool. The findings indicate that most respondents agreed and strongly agreed that the narrative videos were informative, engaging, and able to represent the identity of Kampung Budaya Polowijen clearly. The study concludes that the developed narrative videos are well accepted and beneficial in promoting Kampung Budaya Polowijen as a cultural tourism destination to both domestic and international audiences.